Avaliação de protocolos de descarte e desidratação da escuma acumulada no interior de separadores trifásicos de reatores UASB - Carlos Andres Diaz Florez (2016)
The scum which is accumulated within the three-phase separator (TPS) is considered one of the main operational problems of UASB reactors in domestic waste water treatment systems. In this sense, the main purpose of this research was to evaluate routines of scum dischargefrom the inner of TPS. Moreover, were evaluated the stages of sieving, thickening and drying scum looking for the establishment of alternatives of management. The experimental apparatus is located in the Research and Training Center in Sanitation- UFMG / COPASA (CePTS) in Belo Horizonte - MG. This consisted of a UASB reactor in demonstration scale(useful volume: 16,8 m3), equipped with hydrostatic scum removal device, sieving unit, thickening unit and drying beds. The discharges were executed applying the hydrostatic removal mechanism with variation of operational conditions of discharge frequency, valve opening degree, discharge duration and level of interface scum/biogas in relation with edge of the weir of discharge. The drying was monitored through the total solids (TS) reduction, as well as through beds volume and the evaporated and percolated fractions. In the thickening process were evaluated the contents of total solids (TS), volatile total solids (VTS), chemical oxygen demand (COD) and oil and grease (O&G) from the clarified fraction. Additionally was evaluated the anaerobic biodegradability of the supernatant fraction. The medianefficiencies for the scum removal ranged for 75,6% to 90,1%, with volumes of discharge ranged for 110,9 to 142,2 L, to discharge frequencies of 2 to 5 days. The best operational conditions were obtained for routine with frequency of discharge of 5 days and level of scuminterphase biogas/scum from 2 to 5 cm below the edge of the weir. Was encountered great capacity of the beds for the drying of the scum, reducing total solids from a median concentration of 0,3% (disposal day) to a concentration of 89,0% after five days of drying. In the densification process were obtained median concentrations of TS, VTS, COD, BOD,COD/BOD and O&G in the usual ranges of de domestic sewage which would allow their recirculation. The supernatant fraction of scum had slow rates of methane production (143,4 a 156,2 mLCH4.gVTS-1).